(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study describes the efforts made by teachers to foster students’ learning interest by applying various learning models based on the Deep Learning approach at UPT SPF SMP Negeri 7 Makassar. This research employs a qualitative descriptive method through observation, interviews, and documentation. The research subjects consisted of Social Studies, Informatics, Arts and Culture, and Science teachers who served as model teachers during the principal’s observation of the implementation of the Deep Learning approach. Data were analyzed inductively, emphasizing the interpretation of findings rather than generalization. The results indicate that the model teachers successfully enhanced students’ learning interest through the application of the Deep Learning approach and the use of innovative learning models that created a meaningful, conscious, and enjoyable learning process.